Level and Extent of Financial Literacy of Personnel in the Department of Education, District of Subic, Zambales - Amante, Josua J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the level and extent of financial literacy of personnel in the Department of Education, District of Subic, Zambales. This study is limited to one hundred fifty-eight (158) personnel in the selected schools in the district of Subic. In this study, descriptive research design was adopted. The researcher utilized a self-made survey questionnaire in gathering the data vital to this study. The data gathered from the self-made survey questionnaire were tallied, tabulated, and interpreted accordingly to the following statistical tools: Frequency and Percentage Count, Weighted Mean, Likert Scale and Analysis of Variance. From the given findings, the following conclusions were drawn: First, majority of the respondents were female, age 30-39 years old, bachelor’s degree holder, 0-5 years in service, currently in the teaching position and have no training on financial literacy. Second, the respondents were found to have an awareness of their personal financial literacy in terms of financial management, budgeting, investing and savings. Third, it is also found out that the respondents were aware of their personal extend of the financial literacy skills in terms of trainings and seminars, adherence to policy and their behavior towards financial literacy. Fourth, it was also found out that there was a significant difference in the level of financial literacy of the respondents when grouped according to profile variables highest educational attainment and position. Fifth, there is a significant difference on the extent of financial literacy when grouped according to profile variable sex and highest educational attainment. The length of service has a significant difference only on the adherence to policy. Lastly, based on the results of the study, the researcher may recommend a training program to enhance the financial literacy of the respondents. In the light of the findings of the study, the following recommendations were made: 1.) The DepEd Subic District may implement awareness on what is important in financial literacy to their personnel; 2.) the respondents may strengthen their budgeting and investing skills through attending related training offered by the division of Zambales; 3.) the respondents may improve their financial literacy extent through attending trainings and seminars and develop their financial literacy behavior; 4.) DepEd Division of Zambales administrators may ensure the inclusions of financial management, budgeting, investing and savings on the training to improve the level of financial literacy of personnel; 5.) the teaching and non-teaching personnel financial literacy and financial behavior may be improved through attending various trainings and seminars; 6.) the researcher may recommend or propose a training program to enhance the financial literacy of the DepEd personnel; 7.) a replication of this study in other districts within the division of Zambales is suggested for further research.